2004
DOI: 10.1212/01.wnl.0000138428.40673.83
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin, hematoma expansion, and outcome of intracerebral hemorrhage

Abstract: Warfarin did not increase ICH volume at presentation but did raise the risk of in-hospital hematoma expansion. This expansion appears to mediate part of warfarin's effect on ICH mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
412
2
21

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(463 citation statements)
references
References 29 publications
15
412
2
21
Order By: Relevance
“…Oral anticoagulant therapy-ICH carries a short-term mortality rate of over 50% that has failed to improve with time (Aguilar et al, 2007;Sjoblom et al, 2001). Of note, rebleeding is commoner in OAT-ICH compared with ICH in the setting of normal coagulation (Flibotte et al, 2004). Since coagulation cascade activation and thrombin production are important steps in cellular damage and disruption of the BBB following ICH, it seems logical that OAT-ICH will result in a different tissue response than spontaneous ICH as hematomas may contain noncoagulated blood (Levine et al, 2007;Xi et al, 2006).…”
Section: Multiple Models For Multiple Etiologiesmentioning
confidence: 99%
“…Oral anticoagulant therapy-ICH carries a short-term mortality rate of over 50% that has failed to improve with time (Aguilar et al, 2007;Sjoblom et al, 2001). Of note, rebleeding is commoner in OAT-ICH compared with ICH in the setting of normal coagulation (Flibotte et al, 2004). Since coagulation cascade activation and thrombin production are important steps in cellular damage and disruption of the BBB following ICH, it seems logical that OAT-ICH will result in a different tissue response than spontaneous ICH as hematomas may contain noncoagulated blood (Levine et al, 2007;Xi et al, 2006).…”
Section: Multiple Models For Multiple Etiologiesmentioning
confidence: 99%
“…The apolipoprotein E ε2 allele is associated with larger hematomas, which appears to explain its effect on outcome [15]. The relation between oral anticoagulation use and baseline hematoma volume is unclear; some studies have shown increased baseline volumes [16,17], whereas others have not [15,18].…”
Section: Initial Hematomamentioning
confidence: 99%
“…Seventy three percent of patients express some degree of expansion, and 30 to 40% of patients expand more than 33% from baseline volume [13,18,30,31]. The pathophysiological mechanism by which hematoma expansion occurs remains unclear.…”
Section: Hematoma Expansionmentioning
confidence: 99%
See 2 more Smart Citations